CO-OCCURRENCE OF OCULAR MYASTHENIA GRAVIS, TYPE 1 DIABETES MELLITUS AND GRAVES’ THYROTOXICOSIS IN A YOUNG CHILD - Bunari, Siti Nor Raudzah; Teik, Teoh Sze (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION Ocular myasthenia gravis (OMG), type 1 diabetes mellitus (T1DM) and Graves’ thyrotoxicosis (GT) are autoimmune conditions in childhood. However, co-occurrence and sequential onset of these diagnoses is uncommon. It could signify a spectrum of polyglandular autoimmune syndrome type 2 with polygenic inheritance. CASE A 6-year-2-month-old female presented with progressive drooping of both eyelids for the past two months. Chest CT showed normal thymus, and the anti-acetylcholine receptor was positive (4.89 nmo/L) [reference value (RV) <0.25 nmol/L]. The diagnosis of ocular myasthenia gravis was ascertained. She responded well to pyridostigmine. Nonetheless, she presented again at 8 years and 11 months old with polyuria, polydipsia and nocturia for three weeks, and significant weight loss. She had severe DKA requiring intensive care. Biochemical markers were consistent with T1DM: low C-peptide (57 pmol/L), low insulin (4.3 pmol/L), positive anti-ICA (45.61 IU/mL) (RV <28 IU/mL) and antiGAD (98.18 IU/mL) (RV <17 IU/mL), while anti-IA2 was low (<2.5 IU/mL) (RV <28 IU/mL). While her initial thyroid function was normal, thyroid autoantibody screening was positive for anti-TPO (222 IU/mL) (RV <35 IU/mL). Following multiple daily insulin injections, her glycaemic control and weight gradually improved. Ten months later, at 9 years and 10 months old, her HbA1c worsened, and her mother reported a sudden increase in insulin needs with weight loss. She manifested symptoms of hyperthyroidism and was found to have tachycardia, tremors and diffuse goitre. She did not have Graves’ ophthalmopathy; bilateral ptosis remained the same. AntiTSH receptor antibodies were significantly positive (26.30 IU/L) (RV <1.75 IU/L). CONCLUSION OMG in young children is rarely associated with T1DM. Screening for diabetes auto-antibodies should be considered. In T1DM children, GT should be taken into account when there is unexplained weight loss or deterioration in glycaemic control.